ANALISIS KARAKTER MANDIRI DALAM KEGIATAN VIRTUAL OUTDOOR ACTIVITIES SISWA KELAS III SEKOLAH DASAR - Ninis Ayu Suryani; Maretta Ika Putri; Akhmad Saifuddin Zuhri (PROCEEDING UMSURABAYA, 2022)
Outdoor Learning is an activity in the wild or an activity outside the classroom and has a fun nature, because we can see, enjoy, admire and learn about the creation of God Almighty that unfolds in nature, which can be presented in the form of games, observations/observations. , simulations, discussions and adventures as a medium for delivering material. The study wanted to show the application of the character of student independence in participating in virtual outdoor activities for grade 3 students at SD Muhammadiyah 16 Surabaya Elementary School. The research method used in this study is a qualitative research method. The method used is by observation, interviews, documentation, to students and teachers of grade 3 consisting of 111 students with 8 teachers in elementary school. Muhammadiyah 16 Surabaya. Based on the research results, 78% of students are able to prepare virtual outdoor needs independently. In addition, students are also able to capture material changes in form that are practiced in virtual outdoor activities with an attractive appearance.Â Keywords: independent; outdoor activities